Effect of fermented cream with partial substitution of soy protein isolate on bread quality and volatile compounds. (December 2022) - Xu, Dan; Peng, Yulu; Wu, Fengfeng; Jin, Yamei; Yang, Na; Xu, Xueming
Abstract: This study aimed to improve the bread quality, especially aroma, using the fermented cream-soy protein isolate (SPI) flavor and reveal the improvement mechanisms. The cream with partially substituted SPI was fermented by lactic acid bacteria to enhance its flavor and used for bread making. The study also explored the positive effect of fermented cream on bread quality, especially the aroma formation. The bread quality was assessed by sensory evaluation, texture, and color determination, and the changes in bread dough characteristics were evaluated using a rheofermentometer and a dynamic rheometer. Furthermore, the influence of fermented cream-SPI flavor on bread volatile compounds (VOCs) was investigated using gas chromatography–mass spectrometry and principal component analysis. The results showed that the fermented cream-SPI flavor improved the texture of bread by increasing the gas production and the gluten strength of the dough. It reduced the crumb hardness from 337 ± 12 g to 171 ± 6 g and increased the specific volume from 3.51 ± 0.05 g/mL to 4.19 ± 0.06 g/mL. Moreover, the cream-SPI flavor improved the bread aroma by providing VOCs directly (acids, 2-nonanone, 2-undecanone, 2-tridecanone, and δ-dodecalactone) or precursor substances for VOC formation [esters, ( E, E )-2, 4-nonadienal, ( E )-2-nonenal, and 1-octen-3-ol] during the bread-making process. The present study suggested that the partial substitution of SPI in cream after fermentation had great potential as a bread quality improver to enhance both the texture and aroma of bread.